Meningkatkan ekonomi sejak di bangku kuliah melalui digital marketing - Kurniawan, Mochamad Riski Fajar (Maliki Interdisciplinary Journal, 2023)
Currently, technological advances are increasingly sophisticated. In fact, everyone can take advantage of digital technology as a medium for making money through digital marketing. Even students can take advantage of digital marketing as a medium for making additional money. The purpose of this research is to find out how students have improved the economy since they were in college through digital marketing. The method used is a library study approach to research. To find data on literacy studies, refer to books, journals, internet sites, and other people’s research. The results of the research show that digital marketing has great opportunities for everyone, especially students. Advances in digital technologies have opened up new jobs for everyone. With the capital to promote products through digital media, students can earn money because the products being promoted are selling well. Digital marketing is very useful for students, even though in the middle of a busy study, a student can make extra money.